Belajar bahasa Arab Learn Arabic - Qais Faryadi bin Sadrudeen
This multimedia interactive Arabic learning CD covers 20 topics. The CD has been designed to ensure efficient and effective learning through visual clues, sound and large Arabic wordings. Exercises and tests further reinforce the learning.